Peran Jiwa Kewirausahaan dan Nilai Kewirausahaan Terhadap Kemandirian Usaha - Muhammad Taali; Triana Prihatinta; Ardila Prihadyatama (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2019)
The phenomenon of the development of small industries is an interesting thing to study. Given the small industry has special characteristics that are not owned by medium and large industries. This research will focus on the role of the entrepreneurial spirit and entrepreneurial values ​​in its influence on the business independence of small industry players in the Madiun City, East Java, Indonesia. This research will be designed by exploring primary data in the form of a questionnaire and will use 50 small industry samples in the Madiun City, East Java Province, Indonesia. Furthermore, to solve the problem formulation, Structural Equation Modeling will be used as a tool to analyze data. The results of the analysis show that the value of entrepreneurship influences entrepreneurial behavior, entrepreneurial spirit and the value of entrepreneurship influences business independence.